Contextualizing the Universe of PSAK 74 [IFRS 17] in Indonesia and Insurance Industry Vigilance Through the Cosmology of “Yoga Kshema” - Resi Ariyasa Qadri; Yolanda Mayang Sari; Arifah Fibri Andriani; Rahayu Kusumawati (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2022)
This research aims to answer two main questions about the impacts of implementing IFRS 17 on the insurance industry in Indonesia, and the readiness of the industry to implement the latest insurance accounting standard. This study employed the qualitative research inquiry using an interpretive paradigm. The data in this study were sourced from the results of an extensive literature study to synthesize knowledge related to the implementation of IFRS 17 in Indonesia. Several interviews were conducted with academics and insurance practitioners to validate the knowledge. The collected data were analyzed by utilizing the case study analysis procedure. The results of the analysis are used to be conceptually implemented in one of the leading insurance companies in Indonesia. This study concludes that the insurance sector in Indonesia has experienced a major obstacle related to the competence of accountants during the preparation of IFRS 17 implementation. In addition, a major overhaul of the company's accounting information system is necessary to meet all the IFRS 17 requirements. This research contributes to providing insightful knowledge for the Indonesian insurance industry regarding crucial changes in the company's financial reporting system as a result of IFRS 17 implementation.